2021
DOI: 10.15252/embj.2020107500
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism for modulation of functional amyloid and biofilm formation by Staphylococcal Bap protein switch

Abstract: The Staphylococcal Bap proteins sense environmental signals (such as pH, [Ca 2+ ]) to build amyloid scaffold biofilm matrices via unknown mechanisms. We here report the crystal structure of the aggregation-prone region of Staphylococcus aureus Bap which adopts a dumbbell-shaped fold. The middle module (MM) connecting the N-terminal and C-terminal lobes consists of a tandem of novel double-Ca 2+ -binding motifs involved in cooperative interaction networks, which undergoes Ca 2+ -dependent order-disorder conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…The surface-exposed polyproline helix of CupB6 is part of the adhesion domain, and is believed to mediate a range of protein-protein interactions (Rasheed et al, 2016). In S. aureus , Target ID 37 or ‘biofilm-associated surface protein’, mediates intercellular adhesion and biofilm formation, with the N-terminal lobe of the protein identified to have a significant role (Ma et al, 2021). A filtered list of 2035 AMPs known to have both anti-Gram positive and anti-Gram negative activity (from B-AMP v1.0) (Suppl File 11) , were docked with the identified active site regions of the biofilm targets using AutoDock v4.2.…”
Section: Resultsmentioning
confidence: 99%
“…The surface-exposed polyproline helix of CupB6 is part of the adhesion domain, and is believed to mediate a range of protein-protein interactions (Rasheed et al, 2016). In S. aureus , Target ID 37 or ‘biofilm-associated surface protein’, mediates intercellular adhesion and biofilm formation, with the N-terminal lobe of the protein identified to have a significant role (Ma et al, 2021). A filtered list of 2035 AMPs known to have both anti-Gram positive and anti-Gram negative activity (from B-AMP v1.0) (Suppl File 11) , were docked with the identified active site regions of the biofilm targets using AutoDock v4.2.…”
Section: Resultsmentioning
confidence: 99%
“…DEv-Ig domains are common among bacterial adhesins, and while it remains possible that these domains in Esp have host targets, we instead identified a function that required unfolding of these domains into amyloid-like structures that strengthen biofilms. The structurally related proteins Bap and Antigen I/II also have DEv-Ig folds and form amyloid-like structures that localize to biofilms (47,(54)(55)(56), indicating that DEv-Ig folds can have biofilm-related functions in addition to adhesive ones. We found that Esp743 strengthened biofilms, as did Esp452 and the shorter EspDDDK fragment, suggesting that this capacity is resident at the very N-terminal portion of Esp.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of pathogenic bacteria to form biofilms is one of the key issues that must be addressed to maintain public health. It is known that amyloidogenic proteins promote the primary stage of cell adhesion to the substrate, cell aggregation, and are necessary for the formation of the biofilm matrix [49][50][51][52]. There are also facts confirming the possibility of preventing the formation of biofilms using amyloidogenic antimicrobial peptides.…”
Section: Introductionmentioning
confidence: 99%